Do Politicians Reward Core Supporters? Evidence from a Discretionary Grant Program - Björn Kauder; Niklas Potrafke; Markus Reischmann (Center for Economic Studies and ifo Institute (CESifo), 2016)
We investigate whether politicians award intergovernmental grants to core supporters. Our new dataset contains information on discretionary project grants from a German state government to municipalities over the period 2008-2011. The results show that discretionary grants were awarded to municipalities with many core supporters of the incumbent state government. Discretionary grants per capita increased by about 1.4 percent when the vote share of the incumbent party in the state election increased by one percentage point. The fiscal capacity of a municipality does, by contrast, not predict the level of discretionary grants. We propose to trim discretionary project grants to the benefit of formula-based grants.
Keywords: D72; H72; H77; H81; 330; intergovernmental grants; discretionary grants; fiscal equalization; core supporters; electoral motives